1996
DOI: 10.2135/cropsci1996.0011183x003600010008x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Sugarcane Ratooning Ability and the Relationship of Younger Crop Traits to Older Crop Traits

Abstract: The inheritance of ratooning ability and the relationship of traits among crops in sugarcane (Saccharum spp. hyb.) has not been well examined. Ratooning ability (RA) was defined as the second ratoon (SR) crop yield percent of the plant cane yield. A replicated 4-yr test at four locations of 37 genotypes was studied for two three-crop cycles. Broad-sense single-plot heritabilities for RA were low (H _< 17%), while the genetic coefficient of variation of RA was largest for sucrose yield and cane yield (GCV = 14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 0 publications
8
58
0
4
Order By: Relevance
“…Previous studies by Milligan et al (1996) defined ratooning ability as the ratio of second ratoon to plant crop yield and is widely used by sugarcane breeders. Using this data set, an analysis of variance of the ratio of second ratoon to plant crop produced non-significant genotype effects for both sugar yield (P = 0.1622) and stalk population (P = 0.5398), indicating that genotypes had similar ratooning ability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies by Milligan et al (1996) defined ratooning ability as the ratio of second ratoon to plant crop yield and is widely used by sugarcane breeders. Using this data set, an analysis of variance of the ratio of second ratoon to plant crop produced non-significant genotype effects for both sugar yield (P = 0.1622) and stalk population (P = 0.5398), indicating that genotypes had similar ratooning ability.…”
Section: Discussionmentioning
confidence: 99%
“…Although growers may not evaluate such scenarios at the farm, researchers can present possible options from such studies to provide guidance to growers on variety choice. The ratooning index of Milligan et al (1996) used point estimates ignoring the effect of ratooning cycles. Figures 1 and 2 indicate that the effect of ratooning cycles is important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been quantified for cane yield and sucrose content or for derived sucrose yield in breeding programs at various locations, including Australia (Jackson and Hogarth 1992;Mirzawan et al 1994), Florida (Milligan et al 1996;Glaz and Kang 2008), South Africa (Parfitt 2000;Ramburan et al 2012a), Venezuela (Rea and De Souza Vieira 2002), and Argentina (Mariotti and Clariana 1994). All these examples of MET studies encompassed locations spread over relatively large cultivated areas, necessarily made up of environments that are more or less heterogeneous in various regards, such as soil type (Milligan et al 1996;Glaz and Kang 2008) or cultivation practices (Mirzawan et al 1994). Studies providing formal statistical tests of interactions revealed that both GL and GC effects were always significant for all traits surveyed, except on one occasion (Parfitt 2000).…”
Section: Introductionmentioning
confidence: 99%